A tale of two unions: divergent platforms and their constituencies. Issue 15 (27th March 2020) - Merkle, Jessica; Phillips, Michelle
ABSTRACT: The median voter theorem has regularly been used in economics to represent the behaviour of teachers unions. Little empirical work, however, tests whether this framework is a good fit for teachers unions. We examine voting behaviour in union representative elections between the National Education Association and the American Federation of Teachers and find evidence of divergent constituencies. We investigate whether the median voter explains the outcomes of elections in 1977–1979. If both teachers unions select the platform desired by the median voter, there should be no systematic differences in voter preferences for unions. We find that these unions were fundamentally different and attracted distinct voting coalitions. The main implication of this study is that researchers should consider these two unions, and their effect on districts, as distinct.